Response of Two Sesame (Sesamum indicum L.) Cultivars to Nitrogen and Phosphorus Fertilization under Rain Fed Conditions (University of Khartoum Journal of Agricultural Sciences, 2023)
A field experiment was conducted for two consecutive seasons(2002/2003 and 2003/2004) in the Experimental Farm of the Faculty ofAgriculture, University of Sinnar, Abu Naama, Sudan. The objective wasto study the response of two sesame (Sesamum indicum L.) cultivars tonitrogen and phosphorus fertilization under rain fed conditions. Thetreatments were four nitrogen levels (0, 40, 80, 120 kgN/ha) and fourphosphorus levels (0, 50, 100, 150 kgP 2 O5 /ha). Urea (46% N) andtriplesuperphosphate (48% P 2 O5 ) were used as sources of nitrogen andphosphorus, respectively. Two improved sesame cultivars, Khidir andPromo, were used in the study. The experiment was laid out in a split-splitplot design with four replicates. Nitrogen treatments were assigned to themain plots, whereas cultivars and phosphorus treatments were allotted tothe sub and sub-sub plots, respectively. The results showed that bothnitrogen and phosphorus had significant effects on plant height, shoot dryweight, height to the first capsule, capsule number/plant, percentages ofcapsules on the main stem and the branches and seed yield. The cultivarsshowed significant differences in some growth and yield attributes, withPromo exhibiting better growth and giving higher yield than Khidir.There was significant interaction between cultivars and nitrogen on seedyield in both seasons
Keywords: Sesame; Khidir; Promo; nitrogen; phosphorus; Sudan